O ensino de leitura na educação de jovens e adultos em Floriano (PI): realidade e perspectivas - Carvalho, Rosângela Maria de (2013)
This work is in the line of research Reading, Writing, and Teaching and is themed on the teaching of reading in the Education of Youth and Adults (EJA), in the city of Floriano (PI). We show, by means of observation of 20 Portuguese classes and analysis of a questionnaire applied to five educators, as is the teaching of reading in the EJA in the city of Floriano. The aim of this work is to contribute to the improvement of teaching reading in Youth and Adults (EJA) in the state of Piauí. The specific objectives are: to analyze how teaching reading in the fourth stage of Youth and Adults (EJA) the municipal education in the city of Floriano; reading propose guidelines that may contribute to the development of reading the Education of Young and Adults (EJA) the municipal education of said city. To achieve the objectives of this research, embasamo us in studies on teaching reading considering two approaches: the first refers to the treatment given to reading the Textual Linguistics, based on the studies of Adam (2011), Beaugrande (1997), Koch (2009), Koch & Elias (2010), Koch & Travaglia (2011), Marcuschi (2008), Van Dijk (2004, 2012) and by studies of cognition, based on Kleiman (1993, 2011), Kato (1998, 1999) and Smith (1999), the second refers to the reflection on the teaching of reading based on studies of Cintra (2008 ), Cintra and Passarelli (2012 ), Koch (2002 , 2009), Koch & Elias (2010), Lopes, Cobucci & Machado (2012), Marcuschi (2001) , Marquesi (2004, 2007), Solé (1998). The results show the need to work reading taking into account, on the one hand, the mediating action of the educator, the other, the prior knowledge of the reader. Therefore, we present guidelines for reading that can lead learners to develop reading comprehension and thus contribute to a new approach to teaching reading